Reprotoxicity of zinc oxide nanoparticles synthesized with Crataegus monogyna leaves extract: testis and sperm function - F. REMITA; A. TALBI; C. ABDENNOUR; K. KHELILI; Y. BEDOUH; F. HAMOUD; F. DUMAN; Z. BOUSLAMA; R. ROUABHI; M. R. DJEBAR (Studia Universitatis Babeș-Bolyai. Biologia)
This work examines the effect of three doses of zinc oxide nanoparticles (ZnONPs), synthetized with Crataegus monogyna leaves using zinc acetate, on the sperm quality of Wistar rats. Animals were divided into 4 groups; the control group maintained without treatment, while ZNP1, ZNP2, and ZNP3 received respectively 10 mg ZNP/kgbw, 50 mg ZNP/kgbw, and 100 mg ZNP/kgbw by gavage for 15 days. Epididymis sperm was collected for sperm parameters: concentration, live sperm, motility, velocity (VCL, VSL, and VAP), linearity (LIN), amplitude lateral head (ALH), and beat cross frequency (BCF). DNA fragmentation was measured in three samples selected from control, ZNP1, and ZNP2. Testicular and epididymis malondialdehyde (MDA), glutathione (GSH), and glutathione peroxidase (GPx) were evaluated. Compared to the control, ZNP1 has a significant reduction of testicular and epididymis weights, sperm concentration, live sperm, motility, VCL, VSL, VAP, LIN, and BCF, with a significant increase of MDA and a significant decrease of GSH levels. The ZNP2 group demonstrated a significant increase in epididymis weight, a raise in sperm parameters (concentration, motility, VCL VSL, VAP, LIN, ALH, and BCF), and an augmentation in GSH and GPx levels. However, ZNP3 has a significant increase in VSL and ALH while ZNP1 and ZNP2 showed no effect on spermatozoa DNA. interestedly, we found that the lower dose of ZNP1 acted as toxic to testicular and epididymis parameters, while the higher ones may help to improve sperm quality and reduced oxidative stress.